DISCOVERY OF MORE CHANGING LOOK EVENTS IN NGC 1566 - Oknyansky, V. L.; Winkler, H.; Tsygankov, S. S.; Lipunov, V. M.; Gorbovskoy, E. S.; van Wyk, F.; Buckley, D.A. H.; Tyurina, N. V. (Одеські астрономічні публікації, 2019)
We summarize a study of optical, UV and X-ray light curves of the nearby changing look active galactic nucleus in the galaxy NGC 1566 obtained with the Neil Gehrels Swift Observatory and the MASTER Global Robotic Network over the period 2007-2019. We also report on optical spectroscopy using the South African Astronomical Observatory 1.9-m telescope between Aug. 2018 and Mar. 2019. A substantial increase in X-ray flux by 1.5 orders of mag- nitude was observed following the brightening in the UV and optical bands during the first half of 2018 year. After a maximum was reached at the beginning of July 2018, the fluxes in all bands decreased with some fluctuations. The most remarkable re-brightenings in of the light curve following the decline from the bright phase were observed at MJD range 58440-58494 and 58603-58654. The amplitude of the flux variability is strongest in the X-ray band and decreases with increasing wavelength. Low-resolution spectra (Aug 2018) reveal a dramatic strengthening of the broad emission as well as high-ionization [FeX]6374 lines. These lines were not detected so strongly in the past published spectra. The change in the type of the opti- cal spectrum was accompanied by a significant change in the X-ray spectrum. For the last optical spectra (31 Nov. 2018 – 28 Mar. 2019) we see dramatic changes compared to 2 Aug 2018, accompanied by the fading of broad emission lines and high-ionization [FeX]6374 line. Effectively, two changing look (CL) cases were observed for this object: changing to Sy1.2 type and then returning to the low state as Sy 1.8–Sy1.9 type. Some possible explanations of the observed dramatic changes are discussed.